Acute Aortic Dissection Presenting with a Headache: An Easily Missed Life-threatening Emergency - Chahine, Johnny (Cureus, 2018)
Acute aortic dissection is a deadly disease that should be recognized promptly. We report an exceptional case of a 44-year-old African American female who presented with a rapidly progressing severe frontal headache. Initial computed tomography of the brain was negative. The following day, she developed uncontrolled hypertension and worsening headache. Magnetic resonance imaging of the brain was therefore done and showed evidence of acute/subacute ischemic infarcts. The patient was managed as having an ischemic stroke. For that reason, an echocardiogram was done the next day that showed a dilated aortic root and moderate-to-severe aortic regurgitation. This was followed by a computed tomography angiography which showed ascending aortic dissection involving bilateral common carotid arteries. After an urgent surgical intervention, the patient recovered without any sequelae. Patients with an acute dissection can present with atypical clinical features, such as an isolated rapidly progressive headache, which might delay the diagnosis and jeopardize their lives. Hence, high-risk patients with rapidly progressive unexplained severe headaches should be considered for imaging of the aorta.